Tanggapan Siswa, Orang Tua dan Guru terhadap Pembelajaran Jarak Jauh Selama Pandemi Covid-19 (Students, Parents and Teachers’ Responses to Distance Learning During The Covid-19 Pandemic) - Sutia, Cece; Sagita, Sylva (Jurnal Inspirasi, 2020)
This study aims to assess the students, parents and teachers’ responses to online distance learning carried out by SMA / SMK in the Greater Bandung area during the COVID-19 pandemic. Data were collected using questionnaires and interviews. A total of 2701 students, 586 parents and 270 teachers participated in this study. There are several important findings related to online learning during the COVID-19 pandemic. First, many teachers did not analyze the school context regarding the student’s ability to access the learning management system. Many teachers rarely provide feedback on student work. Second, WhatsApp and Google Classroom are the applications most widely used as learning media. Third, there are several obstacles experienced by teachers and students during the implementation of online learning related to internet access and quotas. Fourth, there are still many schools that do not help teachers and students with internet access. Fifth, both students and teachers yearn face-to-face learning activities in the classroom.